TANGGAPAN FISIOLOGIS RHIZOBAKTERI OSMOTOLERAN (Enterococcus flavescens) TERHADAP CEKAMAN OSMOTIK (GLUKOSA) DAN KEASAMAN (ALUMINIUM SULFAT) - , SUMITRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Osmotolerant Rhizobacteria designated as Enterococcus flavescens has been subjected to glucose and acid stress condition to study its physiological response. Cells were cultured in 2 different media : LB (Luria Bertani) and M63 (minimal medium), supplemented with glucose and aluminium sulphate to imposedouble stress condition. Physiological responses of the rhizobacteriaunder environmental stress were observed by measuring its growthandthemetabolitessynthesised. The results of thisstudydemonstrated that the higher glucose concentration, the lower thecell density in M63 medium. On the other hand, in M63 medium, elevated concentration of glucose resulted in higher cell density, despite the fact that the actual cell density in M63 medium was much lower than in LB medium.GC-MS (Gas Chromatography Mass Spectrophotometer) analysis conductedon cells cultivated using LB medium without any treatment (control) and on cells grown under LB medium supplemented with glucose 5% and Al2(SO4)3 500 ppm resulted in several metabolites detected.Two metabolite compounds were identified in control medium, i.e.oxirane andphenol, whilein LB medium supplemented with glucose 5% and Al2(SO4)3 500 ppm, nine metabolite compounds were identified, i.e.phenol, Butanoic acid